Hitlerugend is an Organization That Turned Young People into Nazis - Sh.Sh.Hamrokulova; Norboyev Firdavs Zafarovich (Zien Journals, 2022)
This article is about Hitler, the organization that played a key role in training German youth to be nationalists and racists. The main reason for covering this topic is to reveal that nationalism is very dangerous and that it can lead to bad consequences in the long run.
Keywords: political propaganda; Nazism; Nuremberg; court,